2011
DOI: 10.1097/mnm.0b013e328340c586
|View full text |Cite
|
Sign up to set email alerts
|

Can severely impaired cortical transit predict which children with pelvi-ureteric junction stenosis detected antenatally might benefit from pyeloplasty?

Abstract: Severely impaired cortical transit seems to be a valuable marker of those patients who could benefit from a pyeloplasty, either because of the high probability of postoperative DRF improvement, or because of DRF deterioration in case of an conservative approach. However, a normal cortical transit, as defined in this study, does not exclude the risk of DRF deterioration. Alternatively, the design of this study does not allow excluding the fact that DRF might improve after pyeloplasty despite a normal cortical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Transit time in nonobstructive patients with dilatation is longer when compared to normal patients [8,22]. Studies carried out in recent years show that the evaluation of both prolonged cortical transit time and poor kidney washout is a valuable indicator/marker for patients who can benefit from pyeloplasty [4,29]. Also in our study, the activity remaining in the kidneys in 20th minute was found over 82.8% and 74.2% for Tc99m DTPA and Tc99m MAG-3 respectively and this supports the existence of obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Transit time in nonobstructive patients with dilatation is longer when compared to normal patients [8,22]. Studies carried out in recent years show that the evaluation of both prolonged cortical transit time and poor kidney washout is a valuable indicator/marker for patients who can benefit from pyeloplasty [4,29]. Also in our study, the activity remaining in the kidneys in 20th minute was found over 82.8% and 74.2% for Tc99m DTPA and Tc99m MAG-3 respectively and this supports the existence of obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…74,75 A prolonged parenchymal transit time is not specific to obstruction but increases the likelihood of its presence. The parenchymal transit time calculation is not offered on many commercial systems but can be implemented by following the recommendations in a previously published consensus report.…”
Section: Image Processingmentioning
confidence: 99%
“…3,35,38,57,63,75 Drainage can be quantitated by measuring the residual post-furosemide or postvoid renal counts normalized to the maximum counts. 57,63 As an example, assume the time to peak is 10 minutes and there is still retention in the collecting system after furosemide administration, with a T 1 / 2 of 18 minutes; the patient voids after the study and the postvoid/max count ratio at 30 minutes is 0.10.…”
Section: Interpretation and Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, along with its favorable dosi metry, because of its higher clearance (40%) than that of 99m Tc-DTPA, 99m Tc-MAG3 provides superior diagnostic images and is an agent of choice for the renal scintigraphy in neonates and children. Since future deterioration of renal function cannot be predicted solely based on findings such as sonographically progressive dilation, obstruction, low differential function on diuretic scan 20) , cortical transit A B time is expected to be a reliable predictive marker 21) , and among many technical attempts to evaluate it, visual estimation of cortical transit seems to be the best approach 22) . Serial renal scintigraphy may help physicians in followingup of patients after therapeutic intervention.…”
Section: Clinical Applications 1 Ureteopelvic Junction Obstructionmentioning
confidence: 99%